Alfonso Buch (1969-2010). In memoriam - Revista de Estudios Sociales de la Ciencia y la Tecnología, Redes (Redes. Revista de Estudios Sociales de la Ciencia y la Tecnología, 2013)
Alfonso Buch (1969-2010). In memoriam.